Maternal Knowledge, Attitude, and Practices about Traditional Food Feeding with Stunting and Wasting of Toddlers in Farmer Families - Simanjuntak, Betty Yosephin; Haya, Miratul; Suryani, Desri; Khomsan, Ali; Ahmad, Che An (Kesmas, 2019)
Traditional foods are foods consumed by a certain ethnic group in a specific region. The habit of consuming traditional foods is usually inherited by the family members, including toddlers, of a respective generation. The study aimed to determine relationship of maternal knowledge, attitude, and practices in traditional food feeding with stunting and wasting of toddlers in the farmer families of the Central Bengkulu District. This study employed a cross-sectional design with a sample of mothers with children aged 12–59 months. The sample included a total of 115 farmer families. Data on nutritional knowledge, attitude, practices about traditional food, sex of children, and the number of family members were collected via interviews conducted with the mothers; stunting and wasting status data were collected via height and weight measurements. Data were analyzed bivariately using the chi-square test. Multivariate logistic regression analysis was also used in this study. It was found that there was a relationship between nutritional knowledge of traditional food and nutritional status of weight-for-age (p-value = 0.031), and there was a correlation between nutritional practices of traditional food and wasting incidence (p-value = 0.012). According to the height-for-age index, the nutritional status was related to the maternal knowledge of traditional food, whereas the maternal nutritional practice with traditional food had a significant relationship with the weight-for-age index.